PENGARUH SUPERVISI DAN STRESS KERJA TERHADAP DISIPLIN DAN PRESTASI KERJA TENAGA DI PENDIDIK SMPN1 BAURENO - Azizah , Filla Dika Nur; Indrawati , Mei; Soenarmi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
The purpose of this study is to describe supervision, work stress on discipline and work performance of teacher at SMP Negeri 1 Baureno, Bojonegoro Regency. To analyze the effect of supervision and work stress on work discipline and work performance of educators at SMP Negeri 1 Buareno, Bojonegoro Regency. This research is a causal associative type with a quantitative research approach. The population size in this study was 55 teacher at SMP Negeri 1 Baureno Bojonegoro. The sampling technique is by census sampling, namely all members of the population as the research sample. Methods of data collection with questionnaires and documentation. Data processing techniques using the Partial Least Square (PLS) based Structural Equation Modeling (SEM) method. The results showed work performance, supervision and work stress in the "high" category, while work discipline was in the "very high" category. Supervision has a significant positive effect on both work discipline and work performance. Work stress has a significant negative effect on work discipline and a non-significant negative effect on work performance. Work discipline has a significant positive effect on work performance. Supervision has a significant positive effect on work performance through work discipline. Work stress has no significant negative effect on work performance through work discipline.